SoftCOM AI,autonomous driving telecom network solution - Bing ZHAO; Zhimin LIU; Yiming YUAN; Tao HAN (Dianxin kexue)
At present,AI has risen to become the core strategy for the transformation and upgrading of science and technology in various countries.Under the background of the internet of everything,all walks of life have set off a research boom of AI.The telecom industry is no exception.As the carrier network faces the challenge of digital transformation,the automatic driving of the telecommunication network through AI technology has gradually become the consensus of the industry.Huawei’s SoftCOM AI solution for autopilot and its deployment methods,values and cases were introduced .